Justice: what is it and how can you ensure your patients receive it?. Issue 1 (2nd January 2022) - Bifarin, Oladayo; Stonehouse, David
Abstract : This article discusses the important concept of justice, one of the four ethical principles developed by Beauchamp and Childress (2019) . Gillon (1994) divided justice into three categories: distributive justice, rights-based justice and legal justice. Justice also forms an important part of British values regarding democracy, the rule of law, individual liberty, mutual respect and tolerance of those of different faiths and beliefs. Following an introduction defining what is meant by the term 'justice', the relevant parts of the Nursing Midwifery Council code (NMC, 2018a ) will be identified and presented. There will then follow a discussion on the three categories of justice as laid out by Gillon (1994) and how justice fits in with British values. Finally, this discussion will point towards how justice can be achieved for the patients in your care and the colleagues you work alongside.